The integration of indigenous knowledge in the social studies classroom to promote intercultural competence - Dewi, Kirana Prama; Probosiwi, Probosiwi; Rahmawati, Isna (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
Indonesia is a heterogeneous population that speaks various languages and has a wide range of cultural, racial, religious, traditions, and indigenous knowledge. In our multicultural and globalized society, intercultural competence is becoming more critical. This study aimed to discover how to integrate indigenous knowledge into the social studies classroom to promote intercultural competence. The method used was descriptive qualitative analysis. The subjects of this study were students in two classes and a lecturer. Data collection techniques used were interviews, observation, and a reflective journal. This research used data triangulation techniques to check the data validity. The result showed 1) integrating indigenous knowledge in the social studies classrooms through eight steps: collection and identifying, analyzing, implementing, evaluating students, reflecting the cultural value, evaluating the lesson process, expanding, and sharing, and 2) The intercultural competence students were also identified in the significant increase on four dimensions: knowledge, attitude, skills, and behavior.